2014
DOI: 10.1016/j.fcr.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the glyphosate-resistance gene and of herbicides applied to the soybean crop on soil microbial biomass and enzymes

Abstract: Glyphosate, a broad-spectrum herbicide used for the non-selective control of weeds, inhibits 5enolpyruvylshikimate-3-phosphate synthase, a key enzyme in the synthesis of aromatic amino acids in the shikimic acid pathway in plants, fungi and bacteria, thus impairing the synthesis of proteins required for various life processes. Soybean genetically engineered to be glyphosate resistant (GR or Roundup Ready, RR) represents the most cultivated transgenic crop globally, including Brazil. There are concerns about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 65 publications
0
21
0
2
Order By: Relevance
“…These results are in agreement with our previous studies (Płatkowski and Telesiński 2015a,b). The effect of glyphosate on soil enzymes involved in phosphorus metabolism gave conflicting results: inhibition (Sannino and Gianfreda 2001, Floch et al 2011, Yu et al 2011 and stimulation (Nakatani et al 2014, Cherni et al 2015. Tejada (2009) reported that the effect of glyphosate on phosphatases is higher in sandy soil than in clay soil.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with our previous studies (Płatkowski and Telesiński 2015a,b). The effect of glyphosate on soil enzymes involved in phosphorus metabolism gave conflicting results: inhibition (Sannino and Gianfreda 2001, Floch et al 2011, Yu et al 2011 and stimulation (Nakatani et al 2014, Cherni et al 2015. Tejada (2009) reported that the effect of glyphosate on phosphatases is higher in sandy soil than in clay soil.…”
Section: Resultsmentioning
confidence: 99%
“…3, 4). The effect of glyphosate on soil microorganisms depend on the dosage, soil texture and organic matter content [Giesy et al 2000, Nakatani et al 2014. The results obtained by Tejada [2009] showed that glyphosate effect on phosphatases is higher in light soil than in clay soil.…”
Section: Resultsmentioning
confidence: 88%
“…NPT.2016.1.13 7 (Płatkowski i Telesiński 2015a, 2015b. Wykonane dotychczas badania wskazują zarówno na brak zmian aktywności fosfataz glebowych pod wpływem glifosatu (Cherni i in., 2015;Nakatani i in., 2014), jak i na ich stymulację (Floch i in., 2011;Ying i in., 2011) czy inhibicję (Sannino i Gianfreda, 2001). Zmiany aktywności enzymów biorą-cych udział w przemianach związków fosforu w glebie są spowodowane obecnością w cząsteczce glifosatu grupy fosfonowej (Haney i in., 2000).…”
Section: Wyniki I Dyskusjaunclassified